Dynamics of angiogenesis and cellularity in rabbit VX2 tumors using contrast-enhanced magnetic resonance imaging and diffusion-weighted imaging - Li, Haixia (Oncol Lett, 2018)
A number of studies have demonstrated that dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) may be used to evaluate microvessel density (MVD), and may quantitatively reflect tumor angiogenesis. To investigate the dynamics, including angiogenesis and tumor cellularity, of rabbit VX2 tumors during the 4 weeks following tumor implantation, the present study used DCE-MRI combined with diffusion-weighted imaging (DWI) to scan the tumors at 3 days, and then at 1, 2, 3 and 4-week intervals, following tumor implantation. The dynamics, volume transfer coefficient (K(trans)) and apparent diffusion coefficient (ADC) of the tumor parenchyma were analyzed. Furthermore, the associations between K(trans) and MVD at 4 weeks after tumor implantation were analyzed. Tumor K(trans) was positively correlated with MVD at 4 weeks (r=0.674, P<0.001). Following tumor implantation, the tumor K(trans) level rose for 2 weeks and then began to decline, reaching its lowest point at 4 weeks (P<0.001). ADC values at 1 week were higher than at 3 days, but declined thereafter (P<0.001). Tumor necrosis appeared by 1 week after tumor implantation. The necrosis degree of tumor was gradually increased from the occurrence of necrosis within the 4-week time span of the present study (1 vs. 2 weeks, P=0.008; 2 vs. 3 weeks, P<0.001; 3 vs. 4 weeks, P<0.001). The present study identified that tumor angiogenesis is a dynamic process that serves a function in tumor growth, and that DCE-MRI may reflect tumor parenchymal MVD and be useful in evaluating angiogenesis.